Alkaline earth metal ions mediated coordination separation of valuable organic acids from depolymerization products of lignite. (15th August 2022) - Ding, Zhiwei; Liu, Qian; Hao, Jianxiu; Li, Na; He, Runxia; Zhou, Huacong; Liu, Quansheng
Graphical abstract: Highlights: Coordination separation was proposed to separate BPCAs from lignite depolymerized products. Alkaline earth metal ions showed high selectivity to BPCAs. Varieties of metal ions and pH of solution had significant influences on separation yields and selectivity. Reaction temperature and time mainly affected the separation yields of BPCAs. Abstract: Oxidative depolymerization of lignite to produce valuable organic acids such as benzene polycarboxylic acids (BPCAs) is a potential route to achieve non-energy and value-added utilization of lignite. However, due to the complexity of depolymerization products of lignite, the separation process becomes the bottleneck problem during the utilization of the depolymerization products, which limits seriously the development of this route. In this study, based on the coordination properties of carboxylic acids with metal ions, the coordination separation of BPCAs from depolymerization product mixture via the coordination of alkaline earth metal ions (Mg 2+, Ca 2+, Sr 2+, and Ba 2+ ) was proposed. The separation conditions including pH of the solution, the dosage of metal salts, reaction time, and temperature were studied. The results showed that the route was effective and different metal ions exhibited different separation behaviors towards BPCAs. Ca 2+, Sr 2+, and Ba 2+ showed high selectivity to BPCAs with carboxylic groups ≥ 4 when the pH was around 8 (for Ca 2+ ) or 6 (for Sr 2+ and Ba 2+ ). By comparing the influences of different factors, it was found that the pH value of the mother solution had significant influence on both separation yields and selectivity of BPCAs. The dosage of metal ions, reaction temperature and time mainly affected the separation yields with no obvious influence on the selectivity. The structures of the intermediate formed by BPCAs with metal ions were analyzed, and the results showed that BPCAs were separated out from the mixture via the coordination interaction between metal ions and the carboxylic groups in BPCAs. The metal ions could be reused for 3 times without obvious decrease in the efficiency. The separation process was carried out under near room temperature and used water as the solvent, which is mild and no need of using the organic solvents. The separation selectivity could be simply tuned by controlling the variety of metal ions and the pH of the solution. This work can provide basic data and technical reference for the separation of organic acids from depolymerization products of lignite.